Symulacja złożonych systemów produkcyjnych metodami Monte Carlo - Ałdohin, Iwan P.; Waćkowski, Kazimierz (Wydział Prawa i Administracji UAM, 1977)
A model and a complex analysis methodics of a multiple functioning of production systems are proposed in the paper. The model yields (with an assumed criterion) the optimum relations between elements of the system as well as between the basic production system and its auxiliary sections safeguarding its work. The method of Monte-Carlo and graphic methods of the reconstitution of the production process are adapted.
Simulation of Multi-Production Systems by Monte-Carlo Methods